Corrigendum to “The relationship between nurses’ speaking up about patient safety and nursing work environment in Saudi Arabia: A cross-sectional study” [Belitung Nursing Journal, 2026; 12(2): 198-207] - Rawan Albalawi; Nirvana Abdelrahman Gheith; Ebaa Felemban (Belitung Nursing Journal, 2026)
This corrigendum corrects a clerical error regarding the institutional affiliation of the second and third authors in the original article (DOI: https://doi.org/10.33546/bnj.4233). The authors confirm that this administrative correction does not affect the methodology, data analysis, results, or conclusions of the original study and sincerely apologize for any inconvenience caused.